A Pilot Feasibility Open Trial of an Interpretation Bias Intervention for Parents of Anxious Children. Issue 4 (November 2022) - Beard, Courtney; Beckham, Erin; Solomon, Arielle; Fenley, Alicia R.; Pincus, Donna B.
Highlights: Tested a mobile health interpretation bias intervention in parents of anxious youth. Intervention was feasible and acceptable to parents. Parents adhered to the recommended number of interpretation bias exercises. Results support next phase of testing in a randomized controlled trial. Abstract: Interpretation bias is a transdiagnostic mechanism underlying anxiety. Theoretical models highlight the role of parental interpretation bias in predicting and maintaining child anxiety. However, very few studies have examined parent interpretation bias as a treatment target. The current pilot study tested the feasibility and acceptability of an interpretation bias intervention delivered by a smartphone app, called HabitWorks, in parents of anxious children who self-reported at least mild symptoms of anxiety and negative interpretation bias. Parents of anxious youth (ages 8 to 16) were recruited from the waitlists of three child anxiety clinics. They were asked to complete interpretation modification exercises via the HabitWorks app 3 times per week for 1 month. Participants completed assessments at pre- and post-intervention and 1-month follow-up to assess changes in interpretation bias, anxiety symptoms, and overall perceptions of HabitWorks. Participants ( N = 14 ) (Mage = 44.36; 14.29% men, 85.71% women) completed an average of 13.29 exercises out of the 12 prescribed. Acceptability ratings were high. Interpretation bias, as measured by an assessment version of the intervention exercise, significantly improved from pre- to posttreatment, and these improvements were maintained at the 1-month follow-up. Anxiety symptoms significantly improved from the "mild" severity range to the "none to minimal" range. In this pilot feasibility study in parents of anxious youth, HabitWorks was a feasible and acceptable low-intensity intervention. These preliminary results support a future controlled trial of HabitWorks for parents. Future studies are also needed to test whether targeting interpretation bias in parents has downstream effects on maladaptive parent behaviors and ultimately, child interpretation bias and anxiety.